DAMPAK KEBIJAKAN PERUBAHAN LOT DAN FRAKSI HARGA SAHAM TERHADAP VOLUME PERDAGANGAN DAN KAPITALISASI PASAR - Dela Deva Destianti; Oktafalia Marisa (Journal of Business & Applied Management, 2015)
This research was conducted to determine the impact of stock trading unit (lot size) and a fraction of the stock price policy to the trading volume and market capitalization of the companies listed in the Indonesia Stock Exchange year period 2013-2014. Sample selection methods using purposive sampling and proportionate stratified random sampling. These results indicate that there was no significant difference in trading volume and market capitalization before and after the policy change of trading unit (lot size) and a fraction of the stock priceKey word :Lot size, Fraction, Market capitalization and Paired sample T-Test